Inhibition of rho kinase enhances survival of dopaminergic neurons and attenuates axonal loss in a mouse model of Parkinson’s disease - Tönges, Lars (Oxford University Press, 2012)
Axonal degeneration is one of the earliest features of Parkinson’s disease pathology, which is followed by neuronal death in the substantia nigra and other parts of the brain. Inhibition of axonal degeneration combined with cellular neuroprotection therefore seem key to targeting an early stage in Parkinson’s disease progression. Based on our previous studies in traumatic and neurodegenerative disease models, we have identified rho kinase as a molecular target that can be manipulated to disinhibit axonal regeneration and improve survival of lesioned central nervous system neurons. In this study, we examined the neuroprotective potential of pharmacological rho kinase inhibition mediated by fasudil in the in vitro 1-methyl-4-phenylpyridinium cell culture model and in the subchronic in vivo 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine mouse model of Parkinson’s disease. Application of fasudil resulted in a significant attenuation of dopaminergic cell loss in both paradigms. Furthermore, dopaminergic terminals were preserved as demonstrated by analysis of neurite network in vitro, striatal fibre density and by neurochemical analysis of the levels of dopamine and its metabolites in the striatum. Behavioural tests demonstrated a clear improvement in motor performance after fasudil treatment. The Akt survival pathway was identified as an important molecular mediator for neuroprotective effects of rho kinase inhibition in our paradigm. We conclude that inhibition of rho kinase using the clinically approved small molecule inhibitor fasudil may be a promising new therapeutic strategy for Parkinson’s disease.